The geochemical characteristics of Cretaceous volcanics in southern Hainan Island and implications for tectonic evolution in the South China Sea - Liu, Yang; Fang, Nianqiao; Wang, Zhongbo (Frontiers in Earth Science, 2023)
The southeastern Eurasian plate, where the South China Sea (SCS) is located, lies in a complex tectonic setting between the Pacific and Tethys tectonic belts. It is widely accepted that the tectonics of the SCS area were influenced by subduction in the late Mesozoic, but there is still controversy over whether it was paleo-Pacific subduction or Tethyan subduction. Volcanic activity in the south of Hainan Island was intense during the Cretaceous, and geochemical analysis of the collected basaltic andesite, andesite and rhyolite samples in this study indicate those intermediate-acid series igneous rocks are high-K calc-alkaline or calc-alkaline. Some andesites have high MgO contents and Mg# values (2.04–5.34 wt% and 36.83–55.29; Mg# = 100× Mg2+/(Mg2+ + TFe2+). Light rare earth elements (LREEs) and large ion lithophile elements (LILEs) are enriched in all the samples, but high field strength elements (HFSEs) are depleted. The negative Eu anomalies are more obvious in the rhyolites than andesites. The geochemical characteristics of the volcanic arc igneous rocks show that the mid-Cretaceous tectonic setting of Hainan Island can be classified as an Andean active continental margin. During the mid-Cretaceous, intermediate volcanism occurred in Hainan Island and its adjacent areas. The zircon-saturation temperatures of the acid volcanic rocks in study area exhibit relatively low values (ranging from 746°C–790°C). Unlike igneous rocks forming in the coastal area east of the South China Block at the same time, no A-type granitoids with alkaline dark minerals appear in Hainan Island. During the late Mesozoic, the western SCS, where Hainan Island was located, may not have been affected by the subduction of the paleo-Pacific Plate, but rather Neotethyan subduction which dominated the Cretaceous magmatic and tectonic activities along the western margin of the SCS. This finding helps to understand the late Mesozoic tectonic evolution of the southeastern edge of the Eurasian plate.